An exploratory study on the teaching of pre-reading skills to third-year non-English-major students using New Headway Pre-Intermediate textbook at a university in Hanoi - Lê, Thị Hồng Vân (University of Languages and International Studies, 2017)
In most cases a common problem students experience in reading classes is the feeling that they have inadequate knowledge about the subject they are reading about. However, this feeling may be more complex than generally thought. The problem may not be the lack of background knowledge, but rather the failure to activate that knowledge.